The family of Jesus [compact disc, unabridged] - Kingsbury, Karen (Simon & Schuster, 2014)
Offers a collection of scripturally based short story views of six of the family members of Jesus Christ, including Mary, Joseph, Jesus' brother James, John the Baptist, Zechariah, and Elizabeth.